The Role of Work Engagement in Mediating Job Rotation on Employee Performance at the Regional Secretariat of Bireuen Regency - Ibrahim Ahmad; Syaifuddin; Sofiyan; Salman Faris (Digital Innovation : International Journal of Management, 2024)
This study seeks to examine the function of work engagement as a mediating variable in the correlation between job rotation and employee performance at the Bireuen Regency Regional Secretariat. Although some organizations adopt job rotation to improve skills and mitigate employee monotony, its effect on performance continues to be a subject of contention. We propose that work engagement, an indicator of employee interest and dedication to their tasks, greatly affects the correlation between job rotation and employee performance. This study method adopts a quantitative approach, employing a survey technique with 150 workers of the Bireuen Regency Regional Secretariat as participants. We employed a path analysis model to examine the direct and indirect impacts of job rotation on employee performance via work engagement. The study's findings suggest that job rotation exerts a beneficial albeit statistically inconsequential impact on employee performance. The incorporation of job engagement as a mediating variable demonstrates a favorable and substantial effect on employee performance. Moreover, job rotation via work engagement positively and significantly influences employee performance. The Bireuen Regency Regional Secretariat has demonstrated that work engagement serves as a mediator in the link between job rotation and employee performance. This study indicates that management ought to prioritize enhancing employee work engagement via initiatives that promote job participation and satisfaction, particularly with job rotation, to attain superior performance.